2010
DOI: 10.1109/jlt.2010.2072905
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Offline Physical Layer Impairments Aware RWA Algorithm With Dedicated Path Protection Consideration

Abstract: Abstract-Physical layer impairments accumulate as light propagates through a lightpath in the transparent optical networks. Therefore, it is possible to provision a lightpath, while its quality of transmission (QoT) does not meet the required threshold. Considering the physical layer impairments in the network planning phase gives rise to a set of offline Impairments Aware Routing and Wavelength Assignment (IA-RWA) algorithms. There are very few offline IA-RWA algorithms that consider dedicated path protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In such a case, constraint (14) forces the value of v k j to be 0. The discussions for constraints (13) and (15) are similar.…”
Section: E Modified Ilp For Sol-hmentioning
confidence: 86%
“…In such a case, constraint (14) forces the value of v k j to be 0. The discussions for constraints (13) and (15) are similar.…”
Section: E Modified Ilp For Sol-hmentioning
confidence: 86%
“…Many heuristic algorithms proposed in technical literature (e.g. [18] and [19]) have used this technique by considering demands sequentially, converting an oine RWA into an online RWA.…”
Section: Oine Vs Onlinementioning
confidence: 99%
“…Results showed that for low signal powers the blocking probability was mainly due to the amplifiers noise, whereas for high signal powers the main contribution to the blocking probability came from the FWM effect. Azodolmolky et al thought Q factor was related to the received samples' statistical distribution, in which ASE noise, FWM effect, and XPM effect were modeled respectively according to the means and standard deviations of distributions of received samples [10]. There were also other models such as Eb/No model where Eb was the average energy per bit, the ratio of signal power and duration of each bit, and No was the noise power spectral density, the ratio of the noise power and the noise bandwidth [2].…”
Section: Related Work Of Pli Modelmentioning
confidence: 99%